Microstructure and tribological behavior of W-Mo alloy coating on powder metallurgy gears based on double glow plasma surface alloying technology - Wei, Dongbo; Liang, Hongxuan; Li, Shuqin; Li, Fengkun; Ding, Feng; Wang, Shiyuan; Liu, Zili; Zhang, Pingze (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
In the present paper, plasma surface alloying was implemented on powder metallurgy gears to improve its wear resistance based on double glow plasma surface metallurgy technology. A W-Mo alloy coating was obtained in the process. The morphologies, microstructure and phase composition were investigated by SEM, EDS and XRD. The hardness was examined by Vickers hardness test and nano-indentation test. The tribological behavior of PM gears before and after plasma surface alloying was evaluated on a ball-on-disc reciprocating sliding tribometer under dry sliding condition at room temperature. The results are as follow. The W-Mo alloy coating was dense and homogeneous without defects, which included deposition layer and interdiffusion layer. Microhardness of PM gears before and after plasma surface alloying were 145.8HV0.1 and 344.4HV0.1, respectively; Nano hardness of deposition layer and interdiffusion layer was 5.76GPa, 14.35GPa, respectively. The specific wear rate of W-Mo alloy coating was lower than the original PM gears. The wear mechanism of W-Mo alloy coating was slight adhesive wear. The W-Mo alloy coating prepared by double glow plasma surface alloying technology can effectively improve the surface wear resistance of powder metallurgy gears.